Football, Femininity and Muscle: An exploration of Heteronormative and Athletic Discources in the lives of elite-level women footballers in South Africa - Engh, Mari Haugaa (Gender Studies, 2014)
Normalised constructions of masculinity and femininity within a heteronormative social structure have shaped beliefs about women's capacities, characteristics and bodies, and have constructed a hegemonic feminine ideal that has historically excluded the possibility of being simultaneously feminine and athletic. However, following developments in Europe and North America (such as Title IV and WIS) and the increased production and consumption of globalised sports, new and more athletic feminine ideals have emerged and opened spaces for women to form sporting and athletic subjectivities. As a part of this process, women's football, across the world, has grown exponentially, in popular support and participation rates, since the first World Cup was organised in China in 1991 (Hong, 2004; Cox and Thompson, 2000). In South Africa, the development of structures for women's football was late, and women's football is not yet fully professional. In South Africa football is viewed as a game for men, and it remains a flagship masculine sport that serves to maintain and support masculine domination (Pelak, 2005). Because women's participation in a sport like football is considered a transgression, there is a heightened need to mark women's bodies as feminine, so as to reinforce the heteronormative and dichotomous constructions of male/female and masculine/feminine. This thesis presents an exploration of the ambivalent relationship between empowerment and surveillance as it presents itself in the lives of elite level women footballers in South Africa. It discusses empowerment and surveillance as they appear at the most intimate levels of women's sporting experience, and impact on the ways in which women footballers discipline and regulate their bodies within the expectations of heteronormativity, femininity and athleticism. The discussion is based on qualitative, informal interviews with 18 elite level women footballers in South Africa, 12 of which are currently members of the 5 senior women's national football team, Banyana Banyana. The remaining 6 participants are members of one of Cape Town's oldest and most successful women's football teams. The interviews took place at a national team camp in Pretoria in October 2008, and in Cape Town between August and November 2008. Utilising discourse analysis and postmodern feminist standpoint theory this thesis concludes that the empowerment and transformation sport has the potential to offer women should not be assumed to follow directly from participation. Women's access to sports participation and sporting subjectivities is stratified, and a complex and ambivalent relationship exists between empowerment and surveillance. This tense relationship between is particularly evident in analyses of gender/race/class intersections, heteronormativity and through examining women's participation at a professional level. Although the neo-liberal feminine athletic validates sporting subjectivities and offers women in elite-level South African football an arena for physical expression and freedom, this empowerment is deeply embedded within the regulatory schemes produced through constructions of a heteronormative feminine aesthetic.